An independent race model involving an abort and re‐plan strategy explains reach redirecting movements during planning and execution. (22nd February 2018) - Venkataramani, PrasannaVenkhatesh; Gopal, Atul; Murthy, Aditya
Abstract: Although race models have been extensively used to study inhibitory control, the mechanisms that enable change of reach plans in the context of race models remain unexplored. We used a redirect task in which targets occasionally changed their locations to study the control of reaching movements during movement planning and execution phases. We tested nine different race model architectures that could explain the redirect behavior of reaching movements. We show that an independent GO–STOP–GO model that reflects a plan–abort–re‐plan strategy involving non‐interacting elements successfully explained the various behavioral measures such as the compensation function and the pattern of error response reaction times. By extending the same race model to the execution phase, we could explain the extent and the pattern of hypometric trials. Interestingly, the race model also provided evidence that redirecting a movement during planning and execution shared the same inhibitory mechanism. Taken together, this study demonstrates the applicability of an independent race model to understand the computational mechanisms underlying the control of reach movements. Abstract : An independent GO–STOP–GO model that reflects a plan–abort–re‐plan strategy involving non‐interacting elements successfully explained the compensation function and other behavioral measures in a reach redirect task.